Respuesta :
Simplify 1/4k to k/4
k/4 = 3(-k/4 + 3)
Regroup terms
k/4 = 3(3 - k/4)
Multiply both sides by 4
k = 12(3 - k/4)
Expand
k = 36 - 3k
Add 3k to both sides
k + 3k = 36
Simplify k + 3k to 4k
4k = 36
Divide both sides by 4
k = 36/4
Simplify 36/4 to 9
k = 9
Answer:
k = 9
Step-by-step explanation:
Simplify 1/4k to k/4
k/4 = 3(-k/4 + 3)
Regroup terms
k/4 = 3(3 - k/4)
Multiply both sides by 4
k = 12(3 - k/4)
Expand
k = 36 - 3k
Add 3k to both sides
k + 3k = 36
Simplify k + 3k to 4k
4k = 36
Divide both sides by 4
k = 36/4
Simplify 36/4 to 9
k = 9